Grounding Naïve Physics and Optics in Perception - Ivana Bianchi; Ugo Savardi (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Many adults hold mistaken beliefs concerning the behavior of mechanical motion and reflections. In the field of psychology this has been investigated in the areas of naïve physics and naïve optics. The interesting question regards where these false beliefs come from. Particularly thought-provoking is the case of errors which are at odds not only with (presumably or even actually) known physical/optical concepts, but also with what people would actually perceive. Some errors are in fact consistent with what people see in ecological conditions while others apparently are not. This has led to the former being referred to as perceptual errors and the latter as conceptual errors (Lawson and Bertamini 2006). We propose that many of these ‘conceptual errors’ are generalizations of what can be actually perceived under some conditions that are then incorrectly applied under others. In this sense, they can be thought of as a second way in which perception shapes naïve beliefs.
Keywords: naive physics; naive optics; perceptual errors; conceptual errors